Conceptual and Methodological Foundations for the Development of Medical Law: A View from Uzbekistan - Kutybaeva Elizaveta Duisenbaevna; Kabulov Khozhabai Aldashevich; Amaniyazova Sveta Bayniyazovna; Gulkhatisha Koptleuovna Shagilova (International Journal of Medical Toxicology and Legal Medicine, 2024)
The article examines the conceptual and methodological foundations of the development of medical law in Uzbekistan in the context of modern reforms and the improvement of the healthcare system. Attention is also paid to the significance of medical law as an independent legal branch aimed at ensuring the quality and fair provision of medical services. The article analyzes legislative measures aimed at improving the healthcare system and strengthening medical law in the republic.